2003
DOI: 10.1046/j.1365-2273.2003.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind randomized controlled study of coblation tonsillotomy versus coblation tonsillectomy on postoperative pain

Abstract: This double-blind randomized controlled trial of coblation tonsillotomy versus coblation tonsillectomy uses visual analogue scoring to compare the pain experienced in the 24h postoperative period. No statistically significant difference in pain is demonstrated in the group of 14 patients studied. Tonsillectomy is recommended over tonsillotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 6 publications
0
52
0
1
Order By: Relevance
“…7 In addition, we have found that with coblation the Next day T2 1 L 1 1 0 0 0 0 1 1 2 R 3 1 2 0 0 2 0 1 3 L 0 1 0 1 0 1 0 1 4 R 2 1 2 1 2 1 1 1 5 L 1 1 1 1 2 2 1 1 6 L 1 1 1 2 1 2 2 2 7 L 2 1 1 0 1 1 0 0 8 R 3 3 2 2 2 2 1 dominance of the surgeon's hand does not statistically affect the outcome. We disagree with this point as we have conducted the same study with adults who were able to discern subtle differences between right and left throat pain.…”
Section: Resultsmentioning
confidence: 99%
“…7 In addition, we have found that with coblation the Next day T2 1 L 1 1 0 0 0 0 1 1 2 R 3 1 2 0 0 2 0 1 3 L 0 1 0 1 0 1 0 1 4 R 2 1 2 1 2 1 1 1 5 L 1 1 1 1 2 2 1 1 6 L 1 1 1 2 1 2 2 2 7 L 2 1 1 0 1 1 0 0 8 R 3 3 2 2 2 2 1 dominance of the surgeon's hand does not statistically affect the outcome. We disagree with this point as we have conducted the same study with adults who were able to discern subtle differences between right and left throat pain.…”
Section: Resultsmentioning
confidence: 99%
“…• Partial tonsillectomy: partial Coblation tonsillectomy was found in one study to take longer than complete Coblation tonsillectomy (15 vs. 5-6 min), for adults with recurrent tonsillitis, but this difference was not statistically significant [6] . When partial Coblation tonsillectomy was compared to partial MES tonsillectomy, in 101 children studied by Chang [ 7 ; level 1], there was no significant difference in operative time (28.5 vs. 30.2 min, p = 0.18).…”
Section: Operative Timementioning
confidence: 92%
“…• Bipolar radiofrequency-induced thermotherapy (RFITT) [6]; • Radiofrequency-induced (cold) ablation (Coblation TM ) [7]; • Monopolar electrical knife [8];…”
Section: Introductionmentioning
confidence: 99%